Field measurement and wind tunnel experimental investigation of a supertall building with closely spaced modes under typhoon Mangkhut - Pan, Haoran (2022)
This paper presents the analysis of full-scale measurement of the Leatop Plaza (303m) under a super typhoon (i.e., Mangkhut), during which field data such as wind speed, wind direction, and wind-excited structural response were recorded. The modal properties, e.g., natural frequency, damping ratios, of the building at consecutive short time windows are identified using a Bayesian frequency domain approach, which provides information on the most probable value and identification (estimation) uncertainty. Time-varying and amplitude-dependent features of natural frequencies and damping ratios are investigated, taking into account identification uncertainty. The power spectral density of modal wind load identified from field data also provides an opportunity for benchmarking with the prediction from wind tunnel tests developed at the design stage. As Leatop Plaza has similar stiffness and mass properties along the two horizontal directions, the frequencies of corresponding vibration modes are very similar, which inevitably poses a challenge to modal identification. Issues associated with closely spaced modes are highlighted and further studied via a recently developed theory of achievable precision of ambient modal identification.